Thermoplastic natural rubber (TPNR) as a backbone polymer for metal injection molding - Norita Hassan,; Sahrim Ahmad,; Norhamidi Muhamad,; Mohd Afian Omar,; Noor Azlina Hassan, (Universiti Kebangsaan Malaysia, 2013)
Moldability of metal injection molding (MIM) is dependent on the outward appearance of the resultant feedstock. Properties of the binders used will influence the properties of the feedstock. Stainless steel powder 316L with mean size 22 μm and the binder system consists of three major fractions of paraffin wax, thermoplastic natural rubber and stearic acid with a powder loading of 65 vol. % was investigated. Comparison was also made with existing palm stearin in the binder system replacing the paraffin wax. Kinetic solvent extractions were done to determine the differences between the binder systems. The feedstock was then injected into tensile bar using vertical injection machine. The results showed that there is a slightly time extension during the solvent extraction as a comparison. The feedstock has been successfully injection molded at 190-200°C. Study of thermal analysis such as DSC and TGA has been done as a preparation for the thermal debinding and sintering process. This study demonstrated that a backbone polymer; thermoplastic natural rubber performs best in term of flow stability and compact quality and also saves in processing time.